2021
DOI: 10.1108/cg-08-2020-0325
|View full text |Cite
|
Sign up to set email alerts
|

Does board gender enhance Palestinian firm performance? The moderating role of corporate social responsibility

Abstract: Purpose This study aims to examine how the salient board gender diversity among board directors affects firm performance both directly and indirectly, through the role of corporate social responsibility (CSR) in listed firms on the Palestine Stock Exchange over the period 2010–2017. Design/methodology/approach Based on panel data of 384 observations from all firms listed on the Palestine Security Exchange during the period from 2010 to 2017, this study uses panel data regression to examine the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 64 publications
2
40
0
Order By: Relevance
“…On one side, according to our literature review, board attributes affect largely CSR engagement (Roffia et al, 2021;Cordova et al, 2021;Nwude and Nwude, 2021;Dwekat et al, 2020;Tibiletti et al, 2021;Zaid et al, 2020;Zubeltzu-Jaka et al, 2020;Al Fadli, 2020;Gerged, 2021;Ben Fatma and Chouaibi, 2021;Shahbaz et al, 2020;Al-Mamun and Seamer, 2020;Bhuiyan et al, 2021;Chintrakarn et al, 2021;Rashid, 2021;Beji et al, 2020;Nuber and Velte, 2021;Campanella et al, 2021). On the other side, earlier researchers reported that the firm performance influences the board characteristics (Mak and Kusnadi, 2005;Valenti et al, 2011;Mak and Kusnadi, 2005;Arora and Sharma, 2015;Di Biase and Onorato, 2020;Govindan et al, 2021;Khan et al, 2021;Assenga et al, 2018;Mishra et al, 2021;Alipour et al, 2019;Saleh et al, 2021;Uyar et al, 2020). It would therefore be reasonable and expected that corporate financial performance moderates the relationship between board attributes and CSR; otherwise, the nature and sign of this relationship may vary according to firm's financial results.…”
Section: 24mentioning
confidence: 79%
See 1 more Smart Citation
“…On one side, according to our literature review, board attributes affect largely CSR engagement (Roffia et al, 2021;Cordova et al, 2021;Nwude and Nwude, 2021;Dwekat et al, 2020;Tibiletti et al, 2021;Zaid et al, 2020;Zubeltzu-Jaka et al, 2020;Al Fadli, 2020;Gerged, 2021;Ben Fatma and Chouaibi, 2021;Shahbaz et al, 2020;Al-Mamun and Seamer, 2020;Bhuiyan et al, 2021;Chintrakarn et al, 2021;Rashid, 2021;Beji et al, 2020;Nuber and Velte, 2021;Campanella et al, 2021). On the other side, earlier researchers reported that the firm performance influences the board characteristics (Mak and Kusnadi, 2005;Valenti et al, 2011;Mak and Kusnadi, 2005;Arora and Sharma, 2015;Di Biase and Onorato, 2020;Govindan et al, 2021;Khan et al, 2021;Assenga et al, 2018;Mishra et al, 2021;Alipour et al, 2019;Saleh et al, 2021;Uyar et al, 2020). It would therefore be reasonable and expected that corporate financial performance moderates the relationship between board attributes and CSR; otherwise, the nature and sign of this relationship may vary according to firm's financial results.…”
Section: 24mentioning
confidence: 79%
“…3.5 Financial performance, board attributes and corporate social responsibility: moderation analysis Assuming boards have a potentially critical role to play in mitigating agency problems (Fama and Jensen, 1983;Jensen, 1993), designing and implementing strategy and fostering links between the firm and its external environment (Arora and Sharma, 2015), questions about the impact of board characteristics on firm performance have attracted significant research (Di Biase and Onorato, 2020;Govindan et al, 2021;Khan et al, 2021;Assenga et al, 2018;Mishra et al, 2021;Alipour et al, 2019;Saleh et al, 2021;Uyar et al, 2020). Findings show that the board structure and composition influence the firm financial performance.…”
Section: Ceo-duality and Corporate Social Responsibilitymentioning
confidence: 99%
“…They refer to resource dependence theory (Pfeffer and Salancik, 1978) to predict the relationship between the presence of women on the board and CSR. This theory holds that more diverse boards contribute to better access to resources, reducing dependence on environmental resources, providing different points of view, advice, legitimacy, business contacts and information channels (Duppati et al , 2019; Chen et al , 2019; Chatjuthamard et al , 2021; Amorelli and García-Sánchez, 2021; Bhatt and Bhattacharya, 2015), which leads to an improvement in decision-making dynamics with respect to a firm's strategy (Kachouri et al , 2020) and favoring the practice of CSR activities (Saleh et al , 2021; Cullinan et al , 2019; Shakil et al , 2020). Within the theoretical framework of dependency theory, prior literature attested that BGD provides various perspectives, skills and values (Byron and Post, 2016) that enhance the decision-making (Fernández-Temprano and Tejerina-Gaite, 2020; Lu and Herremans, 2019; Agyei-Mensah, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Third hypothesis H3a is also accepted as 0.03 is less than 0.05 which proves that board gender diversity has a significant positive impact on earnings per share. This relationship was also proved from the study conducted by Saleh et al (2021) using Palestine Stock Exchange listed firms over the period 2010-2017 and results showed that BGD has a positive and significant influence on firm performance with the moderating effect of CSR. Value of R 2 is 0.30 which means that model is fit and cumulative effect of executive compensation, CEO compensation and board gender on EPS is 30%.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 65%
“…The results show that the gender diversity of the board of directors has a positive and insignificant impact on company performance. However, under the moderating effect of corporate social responsibility, it was found that the change from positive insignificant to positive and significant (Saleh et al, 2021). At the same time, Oware, & Mallikarjunappa (2021) used the Indian stock market as a testing ground to study the family management, financial performance and gender diversification of listed companies.…”
Section: Relationship Between Diversity and Organizational Performancementioning
confidence: 99%